Reduction of Residual Impurities in Homoepitaxial m‐Plane (101¯0) GaN by Using N2 Carrier Gas in Metalorganic Vapor Phase Epitaxy. Issue 8 (16th May 2018) - Barry, Ousmane I; Lekhal, Kaddour; Bae, Si‐Young; Lee, Ho‐Jun; Pristovsek, Markus; Honda, Yoshio; Amano, Hiroshi
Abstract : The reduction of unintentional impurities in m ‐plane ( 10 1 ¯ 0 ) GaN homoepitaxial layers is demonstrated by using nitrogen (N2 ), as opposed to hydrogen (H2 ), as carrier gas in metalorganic vapor phase epitaxy (MOVPE). Secondary ion mass spectrometry (SIMS) analysis shows that the impurity levels of residual oxygen (O), carbon (C), and silicon (Si) are decreased by nearly one order of magnitude in N2 ‐grown samples. Although the full width at half maximum (FWHM) values for the on‐axis m ‐plane X‐ray rocking curves of all specimens are quite similar (around 50 arcsec), plan‐view scanning transmission electron microscopy (STEM) measurements reveal a clear reduction of dislocation densities in N2 ‐grown films. Their origin is likely related to an initial surface roughening with H2 carrier gas, which also causes surface faceting resulting in the formation of large four‐sided pyramidal hillocks, while using N2 results in smoother surfaces. Hence, MOVPE growth with N2 carrier gas is an effective method to lower the impurity incorporation in m ‐plane GaN materials in addition to reducing the formation of defects and improving the surface morphology, which can enable the development of high‐performance GaN‐based devices on non‐polar surfaces. Abstract : The benefit of using nitrogen carrier gas for the synthesis of non‐polar ( m ‐plane) GaN is demonstrated for realizing high‐performance electronic devices. Non‐polar GaN materials produced with nitrogen, as opposed to conventional hydrogen carrier gas, feature lower residual impurity levels, smoother surface morphologies, and reduced dislocation densities. These findings pave the way for developing next‐generation GaN devices.